Comparison Of Judicial Decisions on the Validity of Waarmerking Agreements as Evidence in Court - Azahra, Musdalifah; Sulastri (Universitas Islam Negeri Alauddin Makassar, 2026)
Private agreements registered through a notary's waarmerking mechanism are often used in practice as the basis for legal relationships, including in the event of a dispute, where the waarmerking agreement is used as evidence in court. However, a waarmerking agreement still does not have the full evidentiary force of an authentic deed, because the agreement is not drawn up by a notary, but by the parties privately. Therefore, the parties entering into the agreement should understand and comply with the provisions in making the agreement so that the waarmerking agreement has legal force. The research method used is the normative juridical method. The novelty of this research fills the gap by conducting a comparative study of cases of default on waarmerking land sale agreements in the Bandung Appellate Court Decision Number 376/PDT/2021/PT BDG, which declared it